FTO deficiency facilitates epithelia dysfunction in oral lichen planus - Yufeng Fan; Yukai Hao; Yan Ding; Xiangyu Wang; Xuejun Ge (Molecular Therapy: Nucleic Acids)
The fat mass and obesity-associated protein (FTO) is identified as regulating mammalian development and diseases by removing methyl groups from RNAs. However, the roles of FTO in the context of oral lichen planus (OLP) remain unknown. Here, we demonstrated that the protein levels of FTO in the keratinocytes from OLP patients were down-regulated compared to those from healthy participants. At the molecular level, we explained that GSK-3β-induced phosphorylation promoted FTO protein degradation in diseased oral keratinocytes. Using a cell co-culture model, we further confirmed that FTO deficiency facilitated NF-κB activation and apoptosis in oral keratinocytes under inflammatory conditions. Vitamin D receptor (VDR), which plays a protective role in OLP, was mediated by FTO in an RNA N6-methyladenosine (m6A) methylation-dependent way. FTO overexpression failed to suppress NF-κB and caspase-3 activities upon VDR ablation in oral keratinocytes, suggesting that FTO insufficiency damages oral epithelial by targeting VDR. Collectively, these data reveal that FTO deficiency facilitates epithelial dysfunction in OLP by decreasing VDR expression.